Revisiting the links between the Southern Annular Mode and rainfall over the Western Cape region of South Africa - Mahlalela, Precious (Department of Oceanography, 2019)
The winter rainfall region of South Africa displays considerable interannual variability and prevalence to prolonged dry periods. Although not completely understood, a wide range of factors have been highlighted to contribute to this interannual variability. The relatively poor understanding of rainfall variability in this region is of concern considering the low rainfall received in 2015-2017, resulting in the City of Cape Town enforcing severe water restrictions due to dam levels falling dangerously low. The focus of this thesis is on the influence of the Southern Annular Mode (SAM) on rainfall over the region, the possible influence of El Niño Southern Oscillation (ENSO) is also considered. To achieve this, a correlation analysis was conducted using the Marshal (2003) SAM index and station rainfall anomalies over the region for the period 1979 to 2016. The results show that five (three) of the six driest (wettest) years were associated with a positive (negative) SAM phase. However, the relationship is found to be statistically insignificant at a 95% significance level. The relationship is also found to show spatial variability, with strong negative correlations over the West Coast, while a weak positive correlation is observed over the South Coast. Furthermore, a decadal analysis in the relationship found it to be statistically insignificant (at the 95 th significance level) for most of the study period, with an exception of the early winter over the West Coast which shows a strong negative correlation after 2015. A composite analysis showed that dry (wet) winters tend to be associated with a positive (negative) SAM pattern superimposed with a wave number 3 anomaly. In addition, there are La Niña (El ivNiño) – like SST anomalies in the tropical Pacific. These circulation and SST patterns are more or less observed during the generally dry 2015-2017 winters except that winter 2015 shows an El Niño SST anomaly.